The The Application of Nababan's TQA and Mona Baker's Translation Strategies of Translating Cultural Words and in Movie Subtitle “Puss In Boots: The Last Wish” - Habibi, Vidvan Ruzam (JELL (Journal of English Language and Literature) STIBA-IEC Jakarta, 2025)
Abstract: Puss In Boots: The Last Wish is an animated film produced by DreamWorks Animation which is included in the English language film but throughout the film there are many Spanish words. What makes this interesting is the way the producer combines English and Spanish into one unit that gives a strong element of Spanish culture to this film. This film is shown in various countries in the world, this is a challenge for film translators in translating every cultural word in the film. Translation Quality Assessment in the aspect of acceptability is used to determine the quality of translation in this movie, considering that not all viewers understand Spanish culture or language. The results of the acceptability of this movie show quite good results with an average acceptability of translation of 83,3%. However, many cultural words in this movie appear but are not translated, which is an important note for translators because it ignores small details that can reduce the watching experience.